Corona in the Poet's Perspective: A Comparative Literature Study of The Poetry "Bubarnya Agama" and "Syukrān Kurūnā" - Ahmad Hizkil; Mukhotob Hamzah; Tatik Mariyatut Tasnimah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2021)
This study aims to analyze the message of two poems about the Coronavirus pandemic, namely "Bubarnya Agama" and "Syukrān Kurūnā," and reveal the similarities and differences between them the two poems based on their intrinsic and extrinsic elements. This study uses a qualitative method that uses a comparative literature approach. The data collection technique used is the reading, and note-taking technique, namely the author reads carefully and deeply and then notes the important things from the two poems. Meanwhile, the data analysis technique is descriptive-comparative, which describes the intrinsic and extrinsic elements of the two poems and then compares them. The messages contained in the two poems are generated from the results of the meaning and comparison of the elements of the two poems. This study indicates that the poem "Bubarnya Agama" by Said Muniruddin from Indonesia and the poem "Syukrān Kurūnā" by Jabeer Ali Ba'adany from Yemen are two poems that have their characteristics in terms of their intrinsic and extrinsic elements. The two poems are a response from two poets from different countries to the Coronavirus pandemic hitting all parts of the world. Both poets have their perspectives in interpreting the coronavirus pandemic. However, the two poets both see Corona as something that brings wisdom and major changes to humanity's living and religious order.